2022
DOI: 10.1017/s0033291722001271
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive performances across individuals at high genetic risk for schizophrenia, high genetic risk for bipolar disorder, and low genetic risks: a combined polygenic risk score approach

Abstract: Background Individuals with schizophrenia (SCZ) and bipolar disorder (BD) display cognitive impairments, but the impairments in those with SCZ are more prominent, supported by genetic overlap between SCZ and cognitive impairments. However, it remains unclear whether cognitive performances differ between individuals at high and low genetic risks for SCZ or BD. Methods Using the latest Psychiatric Genomics Consortium (PGC) data, we calculated PGC3 SCZ-, PGC3 BD-, and SCZ v. BD polygenic ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(27 citation statements)
references
References 58 publications
1
21
0
Order By: Relevance
“…The complete lack of correlation (Figure 4, Table S3) suggests that the cognitive deficits we observed among affected participants do not reflect overlapping genetic determinants between mood disorders and cognition. This finding is supported by the polygenic risk score (PRS) literature, which shows no correlation between bipolar disorder PRS and cognitive functioning (Ranlund et al 2018, Ohi et al 2022).…”
Section: Discussionsupporting
confidence: 61%
“…The complete lack of correlation (Figure 4, Table S3) suggests that the cognitive deficits we observed among affected participants do not reflect overlapping genetic determinants between mood disorders and cognition. This finding is supported by the polygenic risk score (PRS) literature, which shows no correlation between bipolar disorder PRS and cognitive functioning (Ranlund et al 2018, Ohi et al 2022).…”
Section: Discussionsupporting
confidence: 61%
“…The subjects for this study were 172 patients with SCZ (71 males/101 females, mean age ± SD: 44.8 ± 13.8 years), 75 unaffected FRs (14 siblings/54 parents/7 children, 25 males/50 females, age: 59.5 ± 14.5 years) and 158 HCs (106 males/52 females, age: 36.4 ± 14.4 years). The study sample was recruited from the Schizophrenia Non-Affected Relative Project (SNARP) at Kanazawa Medical University (Kataoka et al, 2020;Ohi et al, 2019aOhi et al, , 2020aOhi et al, , 2020bOhi et al, , 2021aOhi et al, , 2022b. All subjects were of Japanese descent.…”
Section: Subjectsmentioning
confidence: 99%
“…We indicated that the PRSs for SZ, BD and SZ versus BD based on the GWASs from the PGC were higher in SZ patients than in healthy controls (HCs) 14. On the other hand, the PRSs between the case‒control groups highly overlapped 12 14 15.…”
Section: Introductionmentioning
confidence: 96%
“…On the other hand, the PRSs between the case‒control groups highly overlapped 12 14 15. Therefore, we divided participants into decile category groups based on PRSs and found that individuals in higher deciles for SZ PRSs had up to approximately fourfold, sixfold and twofold higher risk of SZ and PRSs for BD and SZ versus BD than those in lower deciles for SZ PRSs, respectively 14. In addition, we investigated differences in cognitive impairments that were a core feature of SZ and BD and that were more prominent in SZ patients than in BD patients16 17 among three genetic risk groups: the genetic SZ risk, genetic BD risk and low genetic risks for SZ and BD groups, stratified by combinations of the PRSs for SZ, BD and SZ versus BD 14.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation